Global assessment of marine and freshwater recreational fish reveals mismatch in climate change vulnerability and conservation effort. (21st July 2021) - Nyboer, Elizabeth A.; Lin, Hsien‐Yung; Bennett, Joseph R.; Gabriel, Joseph; Twardek, William; Chhor, Auston D.; Daly, Lindsay; Dolson, Sarah; Guitard, Eric; Holder, Peter; Mozzon, Christina M.; Trahan, Alexandria; et al.
Abstract: Recreational fisheries contribute substantially to the sociocultural and economic well‐being of coastal and riparian regions worldwide, but climate change threatens their sustainability. Fishery managers require information on how climate change will impact key recreational species; however, the absence of a global assessment hinders both directed and widespread conservation efforts. In this study, we present the first global climate change vulnerability assessment of recreationally targeted fish species from marine and freshwater environments (including diadromous fishes). We use climate change projections and data on species' physiological and ecological traits to quantify and map global climate vulnerability and analyze these patterns alongside the indices of socioeconomic value and conservation effort to determine where efforts are sufficient and where they might fall short. We found that over 20% of recreationally targeted fishes are vulnerable to climate change under a high emission scenario. Overall, marine fishes had the highest number of vulnerable species, concentrated in regions with sensitive habitat types (e.g., coral reefs). However, freshwater fishes had higher proportions of species at risk from climate change, with concentrations in northern Europe, Australia, and southern Africa. Mismatches in conservation effort and vulnerability were found within all regions and life‐history groups. A key pattern was that current conservation effort focused primarily on marine fishes of high socioeconomic value rather than on the freshwater and diadromous fishes that were predicted to be proportionately more vulnerable. While several marine regions were notably lacking in protection (e.g., Caribbean Sea, Banda Sea), only 19% of vulnerable marine species were without conservation effort. By contrast, 72% of freshwater fishes and 33% of diadromous fishes had no measures in place, despite their high vulnerability and cultural value. The spatial and taxonomic analyses presented here provide guidance for the future conservation and management of recreational fisheries as climate change progresses. Abstract : We used a trait‐based approach to perform a global climate change vulnerability assessment of recreationally targeted fish species from marine and freshwater environments. We compared vulnerability to socioeconomic value and conservation effort to determine regions or species where additional conservation focus is needed. We found that 20% of recreational species are vulnerable to climate change with higher numbers in marine environments, higher proportions in freshwater environments. Mismatches in conservation effort and vulnerability were found within all regions and life history groups. These spatial and taxonomic analyses provide guidance for future conservation and management of recreational fisheries under climate change.